Recipient vessel selection in the difficult neck: Outcomes of external carotid artery transposition and end‐to‐end microvascular anastomosis. Issue 2 (17th July 2015) - Garg, Ravi K.; Poore, Samuel O.; Wieland, Aaron M.; Sanchez, Ruston; Baskaya, Mustafa K.; Hartig, Gregory K.
Abstract : Background: Selection of recipient vessels for head and neck microvascular surgery may be limited in the previously dissected or irradiated neck. When distal branches of the external carotid artery (ECA) are unavailable, additional options for arterial inflow are needed. Here we propose high ligation of the ECA and transposition toward the lower neck as an alternative. Methods: After obtaining institutional approval, patients who underwent head and neck tumor resection and simultaneous free flap reconstruction were identified over a 5‐year period. Patients whose recipient artery was listed in the operative report were included. Chart review was performed to identify patient demographics, operative details, and patient and flap complications. In cases where the ECA was used, the artery was traced distally with care taken to protect the hypoglossal nerve. The ECA was then divided and transposed toward the lower neck where an end‐to‐end microvascular anastomosis was performed. Results: The recipient artery used for head and neck microsurgery was available for 176 flaps, and the facial ( n = 127, 72.2%) and external carotid ( n = 19, 10.8%) arteries were most commonly used. There were 0 flap thromboses in the ECA group compared to 3 flap thromboses that occurred with other recipient arteries ( P = 1.00). No cases of first bite syndrome or hypoglossal nerve injury were identified. Conclusions: The ECA may be transposed toward the lower neck and used for end‐to‐end microvascular anastomosis without complication of hypoglossal nerve injury or first bite syndrome. This method may be considered an alternative in patients with limited recipient vessel options for head and neck microsurgery. © 2015 Wiley Periodicals, Inc. Microsurgery 37:96–100, 2017.